2017
DOI: 10.1002/anie.201709712
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Lycoricidine and Narciclasine by Chemical Dearomatization of Bromobenzene

Abstract: The total synthesis of lycoricidine and narciclasine is enabled by an arenophile-mediated dearomative dihydroxylation of bromobenzene. Subsequent transpositive Suzuki coupling and cycloreversion deliver a key biaryl dihydrodiol intermediate, which is rapidly converted into lycoricidine through site-selective syn-1,4-hydroxyamination and deprotection. The total synthesis of narciclasine is accomplished by the late-stage, amide-directed C–H hydroxylation of a lycoricidine intermediate. Moreover, the general appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…Until now, narciclasine has been isolated from the bulbs of narcissus. However, recent studies have successfully demonstrated organic routes for chemical synthesis of narciclasine and its analogs 26,27 . In this study, we show that compounds that are structurally related to narciclasine also display similar activity, albeit at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, narciclasine has been isolated from the bulbs of narcissus. However, recent studies have successfully demonstrated organic routes for chemical synthesis of narciclasine and its analogs 26,27 . In this study, we show that compounds that are structurally related to narciclasine also display similar activity, albeit at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Sarlah's research involves the discovery of new reactivities and guiding principles for organic synthesis and their application towards biologically active natural products and methods development. His group has described a total synthesis of lycoricidine and narciclasine and an arenophile‐mediated dearomative reduction in Communications in Angewandte Chemie .…”
Section: Awarded …mentioning
confidence: 99%
“…Sarlah untersucht neue Reaktivitäten und Leitprinzipien in der organischen Synthese und wendet diese auf den Gebieten der biologisch aktiven Naturstoffe und der Methodenentwicklung an. Seine Gruppe beschrieb eine Totalsynthese von Lycoricidin und Narciclasin sowie eine Arenophil‐vermittelte Reduktion unter Desaromatisierung in Angewandte‐Chemie ‐Zuschriften.…”
Section: Ausgezeichnet …unclassified